Ameana (?) puella defututa. Textkritische Überlegung zu Cat. c. 41 - Hogenmüller, Boris (Hyperboreus, 2021)
In Cat. 41. 1 ambubaia is suggested as an emendation for the transmitted Ameana. The word would refer to the addressee’s status of a professional prostitute, and there are paleographic arguments in its favour.